Code-Switching: A Strategy to Increase Students Participation In Efl Classroom Interaction - Taufiq, M. Aries; Eka Putri, Rahmi; Asmawati, Asmawati (Yayasan Lembaga Studi Makwa, 2022)
This article aims at describing code-switching (CS) as a strategy to increase students’ participation in EFL classroom interaction. Currently, EFL students are discouraged to participate in the classroom. Their English proficiency becomes the major problem initiated this situation. Obligating the students to speak fully English during the classroom interaction forced them to be silent all the time. Code-switching (CS) was considered to offer a solution for this unsatisfied condition in which the students can switch the language whenever they need. This descriptive study was conducted to reveal the role of code-switching in enhancing students’ participation in the classroom interaction. Switching from English to Indonesian demonstrated an improvement of students’ participation in the classroom interaction. This study found that code-switching provided students an opportunity to interact more effectively in the classroom. By switching the language, the students felt more confident to participate in the classroom and they began to be more active during the classroom interaction Abstrak Artikel ini bertujuan untuk menjelaskan alih kode (CS) sebagai sebuah strategi untuk meningkatkan partisipasi siswa dalam interaksi di kelas EFL. Saat ini, siswa enggan untuk berpartisipasi didalam kelas karena rendahnya kemampuan bahasa Inggris yang mereka punya. Mengharuskan siswa untuk selalu menggunakan bahasa Inggris didalam kelas memaksa mereka untuk menjadi siswa yang pasif. Alih kode menawarkan solusi bagi siswa untuk lebih aktif di kelas karena mereka dapat mengalihkan bahasa kapanpun dibutuhkan. Penelitian deskriptif ini dilakukan untuk mengungkapkan peran alih kode dalam meningkatan partisipasi siswa di kelas. Mengalihkan dari bahasa Inggris ke bahasa Indonesia terbukti meningkatkan partisipasi siswa dalam interaksi di kelas. Penelitian ini menemukan bahwa alih kode membantu siswa berinteraksi dengan lebih efektif. Dengan mengalihkan bahasa, siswa merasa lebih percaya diri untuk berpartisipasi di kelas.